Sirtuin 3 Dependent and Independent Effects of NAD+ to Suppress Vascular Inflammation and Improve Endothelial Function in Mice - Xiaoyun Cao; Yalan Wu; Huiling Hong; Xiao Yu Tian (MDPI AG, 2022)
Atherosclerosis is initiated by endothelial cell dysfunction and vascular inflammation under the condition of hyperlipidemia. Sirtuin 3 (SIRT3) is a nicotinamide adenine dinucleotide (NAD+)-dependent mitochondrial deacetylase, which plays a key role in maintaining normal mitochondrial function. The present study tested whether endothelial-selective SIRT3 deletion accelerates vascular inflammation and oxidative stress, and assessed the protective effect of NAD+ to alleviate these changes in endothelial cells and in mouse models of atherosclerosis. We found that the selective deletion of SIRT3 in endothelial cells further impaired endothelium-dependent vasodilatation in the aorta treated with IL-1β, which was accompanied by upregulation of vascular inflammation markers and mitochondrial superoxide overproduction. Excepting the dysfunction of endothelium-dependent vasodilatation, such effects could be attenuated by treatment with NAD+. In human umbilical vein endothelial cells, SIRT3 silencing potentiated the induction of inflammatory factors by IL-1β, including VCAM-1, ICAM-1, and MCP1, and the impairment of mitochondrial respiration, both of which were alleviated by NAD+ treatment. In ApoE-deficient mice fed with a high-cholesterol diet, supplementation with nicotinamide riboside, the NAD+ precursor, reduced plaque formation, improved vascular function, and diminished vascular inflammation. Our results support the SIRT3-dependent and -independent of NAD+ to improve endothelial function in atherosclerosis.